(3GdQSGdI GdOGaYI ddfGS aj GdQO Ydi HYV GdfUQjI GdcGaQjfs
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdi SHMGfg CeG HYO CjOce Gdehdi HJCjjOg Efg hQO Edi cJGH Cdag HYV GdfUQjI s
(3BNQgG (B:s
(3hCTGY HfSNI ddeSJLjHjf jJaGhVhf Hg JTjOG GSJHQGckG Hg ai cd jhe LOjO fLR hGdSdGe HMeO ehdGfG hefg s
(3QSGdI ef QSGFd GdOQhRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds